Pengembangan Model Pembelajaran Kooperatif dengan Metode Market Share Knowledge - Ahmat Taufik; Wawan Juandi (Program Pascasarjana Universitas Ibrahimy, 2018)
Learning model conducted by the teacher to implement this MaSaKo method by using cooperative learning model which includes the preparation of the syllabus and Learning Implementation Plan (RPP) in accordance with the steps of Cooperative Learning MaSaKo Method. Therefore planning is very necessary and influences the learning process so that it becomes directed and runs in accordance with the expected goals of making students active learning so that learning outcomes can be like. The development of the application of cooperative learning model is produce the Market Share Knowledge (MaSaKo) method, this method as a whole can increase student activity and support the achievement of the learning objectives of Islamic Religious Education. Besides that, it can also be seen that cooperative learning model is also able to improve critical and analytical thinking skills.